Village Health TV for Stunting Prevention in Efforts to Improve Toddler Health in Kalijirak Village, Tasikmadu, Karanganyar, Central Java - Kartinawati, Erwin; Suwarni, Anik; Khoirul Anwar, Ahmad; Putri Suhendar, Rachmalia; Eq Ganiswari, Talitha; Fakhri Fathony, Adib (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Stunting is a problem that requires joint efforts. Stunting is a growth disorder due to chronic malnutrition that can have long-term impacts on children's physical health and cognitive development. Kalijirak Village, Tasikmadu, Karanganyar, Central Java, faces this challenge with a significant prevalence of toddler stunting. To address this problem, the village health TV program was launched as one of the intervention efforts. This program aims to increase public awareness and knowledge about the importance of balanced nutrition, healthy eating habits, and good sanitation, especially for pregnant women and children during the first thousand days of life. Village health TV is an effective communication medium to disseminate health information to the community, especially in areas difficult for health workers to reach. This program educates families about stunting prevention through informative and practical videos adapted to local conditions. With a community-based approach, this program is expected to reduce the prevalence of stunting and improve the health of toddlers in the village, ultimately impacting future generations' quality of life.